2002
DOI: 10.1139/w01-126
|View full text |Cite
|
Sign up to set email alerts
|

Glycine and alanine dehydrogenase activities are catalyzed by the same protein inMycobacterium smegmatis: upregulation of both activities under microaerophilic adaptation

Abstract: Microaerophilic adaptation has been described as one of the in vitro dormancy models for tuberculosis. Studies on Mycobacterium tuberculosis adapted to low oxygen levels showed an enhancement of glycine dehydrogenase (deaminating) activity. We studied the physiology of the fast-growing, nonpathogenic strain of Mycobacterium smegmatis ATCC 607 under low oxygen by shifting the actively growing M. smegmatis cells to static microaerophilic growth conditions. This shifting of M. smegmatis culture resulted in a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Expression of ald is upregulated in M. tuberculosis upon nutrient starvation (7) and in M. marinum during persistence within the granulomas of infected frogs (10). L-Alanine dehydrogenase production and activity were also increased when M. tuberculosis and M. smegmatis were shifted from aerobic to anaerobic growth (21,31,34). In contrast, Western blotting has failed to detect L-alanine dehydrogenase in BCG, even though the ald gene has been identified by DNA hybridization (2).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of ald is upregulated in M. tuberculosis upon nutrient starvation (7) and in M. marinum during persistence within the granulomas of infected frogs (10). L-Alanine dehydrogenase production and activity were also increased when M. tuberculosis and M. smegmatis were shifted from aerobic to anaerobic growth (21,31,34). In contrast, Western blotting has failed to detect L-alanine dehydrogenase in BCG, even though the ald gene has been identified by DNA hybridization (2).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the ald gene as well as the synthesis and activity of Ald were observed to be increased under oxygen-limiting conditions in M. tuberculosis and Mycobacterium smegmatis (2)(3)(4)(10)(11)(12)(13)(14). Other studies reported that expression of the ald gene was upregulated in Mycobacterium marinum during persistence within its host granulomas and in M. tuberculosis under nutrient starvation conditions (5,15).…”
mentioning
confidence: 89%
“…The enzyme forms a hexamer of identical subunits with the N-terminal catalytic domain and the C-terminal NAD(H)-binding domain (6, 7). Ald was shown to be one of the major antigens found in culture filtrates of Mycobacterium tuberculosis (8,9).Expression of the ald gene as well as the synthesis and activity of Ald were observed to be increased under oxygen-limiting conditions in M. tuberculosis and Mycobacterium smegmatis (2)(3)(4)(10)(11)(12)(13)(14). Other studies reported that expression of the ald gene was upregulated in Mycobacterium marinum during persistence within its host granulomas and in M. tuberculosis under nutrient starvation conditions (5, 15).…”
mentioning
confidence: 99%
“…Granuloma-specific activation of the M. marinum ald gene encoding alanine͞glycine dehydrogenase (30,31) is of particular interest. In M. tuberculosis this enzyme catalyzes the formation of alanine and͞or glycine (31,32) and is a major secreted antigen that is not secreted by the nonpathogenic vaccine strain M. bovis, bacillus Calmette-Guérin (33).…”
Section: Marinum Causes a Silent Long-term Infection In Frogs Withmentioning
confidence: 99%
“…In M. tuberculosis this enzyme catalyzes the formation of alanine and͞or glycine (31,32) and is a major secreted antigen that is not secreted by the nonpathogenic vaccine strain M. bovis, bacillus Calmette-Guérin (33). Also of particular interest is the granuloma induction of the M. tuberculosis pknB homologue encoding a protein serine͞threonine kinase (PSTK) (30,34).…”
Section: Marinum Causes a Silent Long-term Infection In Frogs Withmentioning
confidence: 99%